Northwest History. Alaska. Floods & Flood Control. (1937)
Fairbanks Still Is Under Water. FAIRBANKS SJILL IS UNDER WAtER FAIRBANKS, Alaska; May 15. (A>)—Three-quarters of this-interior Alaska metropolis remained under waster today as ice jams continued to dam the flooding Tanana and Chena rivers. Mayor E. B. Collins said the city was in no immediate need of outside disaster assistance. The temperature dropped to 26 above zero last night but the streams continued to rise slowly from melting snows. The lower valley is virtually bare of snow but the mountains and the upper Tanana valley are sending their runoff into the ice-dammed streams. An aerial survey indicated ice was clearing rapidly from the Chena here and its neighboring Yukon tributary, the Tanana, but that Fairbanks is not yet out of The flooded sections of the city were under from a few inches to several feet of water, with about half the residences abandoned and the homeless sleeping in public buildings and hotels. The water had receded from its all-time record flood crest, set yesterday when the Chena was gauged at 13 feet 2 inches above the summer normal. The previous record, 12 feet 6 inches, was set during heavy rains September 1, 1930.